Electrochemical treatment of irradiated nuclear graphite; Journal of Nuclear Materials; Vol. 526 - Bespala E. V. Evgeniy (Evgeny) Vladimirovich; Antonenko M. V. Mikhail Viktorovich; Chubreev D. O. Dmitry Olegovich; Leonov A. V. Aleksey Vyacheslavovich; Novoselov I. Yu. Ivan Yurievich; Pavlenko A. P. Anastasiya Pavlovna; Kotov V. N. Vasily Nikolaevich (2019, 2019)
Title screen